Konsep Tasawuf Menurul Al-Ghazali Dalam Kitab Minhajul Abidin - Adnan Adnan (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This paper aims to analyze al-Ghazali's Sufism thoughts in the book Minhajul Abidin. The research method used is library research. Therefore, the basic analysis that the author uses is the method of content analysis (content analysis). The conclusion concludes that al-Ghazali's Sufism, its relevance to worship, is an inseparable unit, because worship is the actualization of morality that comes out of a sense of service and is full of sincerity. Worship has stages, all of which require several spiritual (sufistic) stages, as a process of worship. Of all these Sufistic values, al-Ghazali always uses knowledge, things and 'charity, cognitive, affective and psychomotor). With the first stage of knowledge, then he will do ('amal) as the second stage, namely repentance. The third stage he faces as a barrier in worship (uqbat al-awa'iq). The fourth stage is sustenance and various calamities that befall it. The fifth stage is the impetus in worship ('uqbat al-bawa'is) namely with khauf (fear) and raja (full of hope). The stages are the stages of destruction (uqbqt al-qawadih). The last stage is praise and gratitude ('uqbat al-hamd wa al-syukr)